Standardized vs. manufacturer leaflet techniques for inhalation devices: A randomized controlled trial - Takahashi, Emiri; Saito, Yurina; Maeda, Eri; Okada, Yuko; Takahashi, Yuta; Doi, Nobuyuki; Horie, Takeo; Araki, Takuya; Obayashi, Kyoko; Suzuki, Asuka (Universitas Padjadjaran (Unpad), 2025)
Variations in inhaler leaflet information may affect the understanding of inhalation techniques.We aimed to determine the effectiveness of standardized and package leaflets in describing correct inhaler usage and to identify any existing pitfalls. This prospective, randomized, open-labeled, blinded endpoint study with a 2 × 2 factorial design was conducted in August2019. We included 38 pharmacy students who did not use inhalers and allocated them into 4 groups: 2 groups used standardized leaflets (with 1 and 2 devices, respectively), while the other 2 groups used package leaflets (with 1 and 2 devices, respectively). The participants were instructed on the essential techniques of using each inhaler and asked to practice using the assigned leaflets until the procedures were completely learned. The primary outcome was evaluated the following day as the score rate (%) of the technique. The effectiveness of leaflets stratified by the number of devices was tested using a two-way analysis of variance with an interaction term. We compared techniques with different implementation rates between groups to identify potential pitfalls. The differences and 95% confidence interval in the score rate (%) between the groups using standardized or package leaflets were significantly different in the two-device group analysis. The implementation rate of certain instructions between the two-device groups was higher when using standardized leaflets for both devices. Standardized leaflets enhanced the comprehension of inhalation techniques for multiple devices due to their normalized wording. These findings may help improve package leaflets and healthcare professionals' instructions, thereby promoting appropriate inhaled medication use.